Health claims in Brazil: helping the public or giving misleading information? - Stangherlin, Isadora do Carmo; Raupp, Monique (Revista de Administração da UFSM, 2017)
The first phase of this study consisted of reviewing the literature related to food labels and its national and international legislations. After that, selected pre-packaged food labels were analyzed in a supermarket situated in the city of Porto Alegre, south of Brazil, considering their nutrition and health-related claims (NHC). From that, the main objective of this study was to identify and analyze these claims. From the products comprised in 9 different food categories, 87 had at least one NHC and, therefore, composed the group of analysis. Most of the claims consisted of nutrition claims (66,53%), followed by health-related ingredient claims (20,34%) and health claims (13,14%). The most common nutrition claims consisted of vitamins (44,2%), with vitamin C representing almost a quarter of the vitamin claims. Regarding health-related ingredient claims, more than a half of them comprised of the lack of conservatives in the food. Health claims consisted mostly of subjective sentences implying that the consumption of the food in question was a "healthy choice" or "source of health". Consumers should know how to evaluate these claims when choosing a food product, avoiding possible misunderstanding.